Immune-Enhancing Effects of Lactobacillus plantarum 200655 Isolated from Korean Kimchi in a Cyclophosphamide-Induced Immunocompromised Mouse Model - Kim, Kyeong Jin; Paik, Hyun-Dong; Kim, Ji Yeon (Journal of microbiology and biotechnology, 2021)
In this study, we evaluated the immune-enhancing activity of kimchi-derived 200655 on immune suppression by cyclophosphamide (CP) in ICR mice. Animals were fed distilled water or 1×10 colony-forming unit/kg B.W. 200655 or GG as a positive control for 14 days. An in vivo model of immunosuppression was induced using CP 150 and 100 mg/kg B.W. at 7 and 10 days, respectively. Body weight, spleen index, spleen weight, and gene expression were measured to estimate the immune-enhancing effects. The dead 200655 (D-200655) group showed an increased spleen weight compared to the sham control (SC) group. Similarly, the spleen index was significantly higher than that in the CP-treated group. The live 200655 (L-200655) group showed an increased mRNA expression of tumor necrosis factor-alpha (TNF-α) and interleukin (IL)-6 in splenocytes. Also, the iNOS and COX-2 mRNA expression was upregulated in the L-200655 group compared to the CP-only (SC) group. The phosphorylation of ERK and MAPK was also upmodulated in the L-200655 group. These results indicate that 200655 ameliorated CP-induced immune suppression, suggesting that 200655 may have the potential to enhance the immune system.